Wheat Seed Gall Nematode Anguina Tritici in Duhok Province, Kurdistan Region - Iraq and its Biology. - Ami, Sulaiman N.; Taher, Ibrahim I. (Science Journal of University of Zakho, 2013)
A survey of several wheat fields at Duhok province during 2010 and 2011 was carried out in Slevani (Duban) plain, Kemeka and Bakhetmi villages, fields around Semel city and other fields along roads of Kora and Kemeka to determine infection percentage by Anguina tritici . Highest infection during 2010 was 11% and 10.4% in wheat fields of Kemeka and Bakhetmi respectively, whereas the lowest was 0.56% in wheat field of Bakhetmi village during 2011.A tritici completed its life cycle in 135- 165 days under field conditions at Faculty of Agriculture and Forestry, Semel-Duhok. Dimensions of Females were 2400 × 132.55 µm, whereas for males was 1790 × 82.19 µm and for second stage Juveniles (J2) and eggs were 490 × 24.9 µm and 94.5 × 38.7 µm respectively.
Keywords: The